Effect of polyethylene glycol on feeding behaviour of dairy goats browsing on bushland with different herbage cover - Decandia M.; Molle G.; Sitzia M.; Cabiddu A.; Pampiro F.; Ruiu P.A. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
36 Sarda goats, at the end of lactation, browsing on a lentisk-based bushland were studied. They were in two groups browsing 7 hours daily on 2 plots with different woody and herbaceous cover proportions: low (W) and high (H). Each group was divided into two subgroups: with PEG supplementation (PS) and no PEG supplementation (PU). Feeding behaviour was different: H-goats had a higher grazing time. Treatments did not affect intake. The percentage of the species eaten by the goats was different in the two groups. PEG affected the botanical composition of the diet. PS ate more tanniniferous species than PU. The different percentage of herbage cover as well as the PEG affected milk yield and composition. There was a significant effect of herbage-cover ï PEG interaction. Milk urea was affected by herbage cover and PEG supplementation. The effect of PEG strictly depends on pasture composition. Its efficacy as antitannic supplement is higher when pastures have a high proportion of tanniniferous species.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)